2017
DOI: 10.1111/ajo.12672
|View full text |Cite
|
Sign up to set email alerts
|

The Great Divide: Country of birth as a risk factor for obstetric anal sphincter injuries

Abstract: BackgroundObstetric anal sphincter injuries (OASIS) can complicate up to 6% of births and are a major contributor to preventable maternal morbidity. Asian women have a risk of third and fourth degree perineal tears up to four times greater than women of other ethnicities in the same community, but the lack of differentiation of Asian women into regional groups has limited insight into the reasons behind their increased risk.AimsTo investigate risk of OASIS associated with country of birth.MethodsThis was a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
(19 reference statements)
1
8
1
Order By: Relevance
“…The risk factor of ethnicity was not investigated in this audit as the primary outcome was if perineal protection was effective at reducing the incidence of OASIS. The impact of ethnicity has been reported elsewhere, and showed that women of South Asian country of birth were at increased risk of OASIS 20 …”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations
“…The risk factor of ethnicity was not investigated in this audit as the primary outcome was if perineal protection was effective at reducing the incidence of OASIS. The impact of ethnicity has been reported elsewhere, and showed that women of South Asian country of birth were at increased risk of OASIS 20 …”
Section: Methodsmentioning
confidence: 62%
“…This was a retrospective observational audit over two 36-month time periods, before and after implementation of the 'Please Squeeze' program at a tertiary level hospital. This unit delivers over 5500 babies per annum and cares for women from very diverse ethnic backgrounds, 20 making it an ideal study population.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several demographic factors have been identified as associated with OASIs. Asian ethnicity, maternal older age, first-time mother and giving birth in public hospitals are all associated with an increase in the risk of OASIs [6][7][8] . Instrumental vaginal birth, including forceps and vacuum births, has been identified as a major risk factor for OASIs 7,9 .…”
Section: Introductionmentioning
confidence: 99%